2010
DOI: 10.1002/chem.201001486
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Boron‐, Silicon‐, and Tin‐Bridged ansa‐Cyclopentadienyl–Cycloheptatrienyl Titanium Complexes (Troticenophanes)

Abstract: A novel one-pot method was developed for the preparation of [Ti(η(5)-C(5)H(5))(η(7)-C(7)H(7))] (troticene, 1) by reaction of sodium cyclopentadienide (NaCp) with [TiCl(4)(thf)(2)], followed by reduction of the intermediate [(η(5)-C(5)H(5))(2)TiCl(2)] with magnesium in the presence of cycloheptatriene (C(7)H(8)). The [n]troticenophanes 3 (n=1), 4, 8, 10 (n=2), and 11 (n=3) were synthesized by salt elimination reactions between dilithiated troticene, [Ti(η(5)-C(5)H(4)Li)(η(7)-C(7)H(6)Li)]⋅pmdta (2) (pmdta = N,N'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
20
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 125 publications
8
20
1
Order By: Relevance
“…The 13 C NMR spectrum displays three and four signals for the C 5 H 4 and C 7 H 6 carbon atoms with the ipso-carbon atoms appearing at δ = 97.2 and 87.0 ppm, respectively. [5b,22,23] The results indicate, however, a less strained structure for 2 compared with the SiMe 2 (λ max = 663 nm) [24b,24c] and SnMes 2 (λ max = 667 nm) [27] analogues. The 119 Sn NMR spectrum of the bridging tin atom in 2 shows a single resonance at δ = -50.2 ppm, which is slightly upfield shifted compared with that reported for [(η 5 -C 5 H 4 )Fe(η 5 -C 5 H 4 )]SntBu 2 (δ = -23.7 ppm).…”
Section: Synthesis and Characterization Of Di-tert-butylstanna[1]trotsupporting
confidence: 81%
See 1 more Smart Citation
“…The 13 C NMR spectrum displays three and four signals for the C 5 H 4 and C 7 H 6 carbon atoms with the ipso-carbon atoms appearing at δ = 97.2 and 87.0 ppm, respectively. [5b,22,23] The results indicate, however, a less strained structure for 2 compared with the SiMe 2 (λ max = 663 nm) [24b,24c] and SnMes 2 (λ max = 667 nm) [27] analogues. The 119 Sn NMR spectrum of the bridging tin atom in 2 shows a single resonance at δ = -50.2 ppm, which is slightly upfield shifted compared with that reported for [(η 5 -C 5 H 4 )Fe(η 5 -C 5 H 4 )]SntBu 2 (δ = -23.7 ppm).…”
Section: Synthesis and Characterization Of Di-tert-butylstanna[1]trotsupporting
confidence: 81%
“…[25b] The stanna [1]troticenophane was successfully synthesized by using sterically demanding mesityl substituents, which provide here the necessary steric protection for the isolation of the desired complex, because attempts to prepare analogous compounds by using less bulky methyl or n-butyl substituents at the tin atom afforded oily mixtures of unidentified products. [27] Furthermore, di-tert-butylstanna [1]ferrocenophane polymerizes much more rapidly than the dimesityl derivative (see above), which indicated that the tBu 2 Sn moiety in the bridge is more appropriate for ROP than Mes 2 Sn. [27] Furthermore, di-tert-butylstanna [1]ferrocenophane polymerizes much more rapidly than the dimesityl derivative (see above), which indicated that the tBu 2 Sn moiety in the bridge is more appropriate for ROP than Mes 2 Sn.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetically equivalent Cht carbon atoms in the 13 C NMR spectra of 2, 3, 6, 7, 9, 10 and 12 are observed as singlet resonances between 85.5 (9) and 89.1 ppm (12). These values are close to that reported for the C 7 H 7 carbon NMR signal in troticene (86.4 ppm) [26]. The 13 C NMR resonance for the quaternary tBu carbon atoms in 3 is found at 36.0 ppm with 1 J( 13 Ce 117/ 119 Sn) ¼ 423.7/402.3 Hz, which falls in the expected range for a four-coordinate tin atom [33].…”
Section: Synthesis and Spectroscopic Characterization Of Cp-functionasupporting
confidence: 75%
“…Recent developments involved the use of nBuLi/pmdta (pmdta ¼ N,N 0 ,N 0 ,N 00 ,N 00 -pentamethyldiethylenetriamine), affording [(h 7 -C 7 H 6 Li)Ti(h 5 -C 5 H 4 Li)]$pmdta (1a), which can conveniently be isolated as a dimeric species in crystalline form ( Fig. 2) and subsequently be employed for the preparation of troticenyldiphosphanes such as [(h 7 -C 7 H 6 PPh 2 )Ti(h 5 -C 5 H 4 PPh 2 )] (dppti) [25] and various boron-, silicon-and tin-bridged [1]-and [2]troticenophanes [26].…”
Section: Introductionmentioning
confidence: 99%
“…[131][132][133][134] Conversely, oxidative addition of the BdB bond within [2]borametalloarenophanes 38 was reported to proceed smoothly and in high yields with platinum(0) phosphine complexes to give the corresponding bis(boryl)platinum(II) complexes 39 (Scheme 37). [135][136][137] Subsequent addition of these complexes to alkynes gave the ansa-bis(boryl)alkene products.…”
Section: Metal Activation Of Halide-or Amine-substituted Diboron Compmentioning
confidence: 99%